Inflammation and Stroke Risk: A New Target for Prevention - Kelly, Peter J; Lemmens, Robin; Tsivgoulis, Georgios (Stroke (1970), 2021)
New therapeutic approaches are required for secondary prevention of residual vascular risk after stroke. Diverse sources of evidence support a causal role for inflammation in the pathogenesis of stroke. Randomized controlled trials of anti-inflammatory agents have reported benefit for secondary prevention in patients with coronary disease. We review the data from observational studies supporting a role for inflammation in pathogenesis of stroke, overview randomized controlled trials of anti-inflammatory therapy in cardiac disease and discuss the potential implications for stroke prevention therapy.